Komunitas Muslim Uni Soviet Dalam Melawan Rezim Stalin 1941-1945 (Kajian Perlawanan Turkestan Legion) - Muhamad Azisy Ramdani; Nana Supriatna; Yani Kusmarni (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2019)
This research elaborated the Turkestan’s life Muslim community in 1941 – 1945 under the Soviet Union. This research made based on researcher’s interest in the history of the Soviet Union’s Muslim community especially the Muslim community in Turkestan whowere in an apprehensive extreme condition when they were under the Stalin regime rule. That was the reason why Turkestan’s Muslim community finally fought back. The research aimed to identify the Turkestan Legion’s effort in fighting back Stalin’s regime. The method was the historical method. Turkestan’s Muslim community fought backbecause Stalin made a discriminative rule and disserve Turkestan’s Muslim community, such as prohibiting the religious freedom and occupied over all natural resources in Turkestan, which resulting poverty and hunger for Turkestan’s Muslim community because Turkestan got nothing from them. Therefore, when Germany invaded the Soviet Union on 22 June 1942, it benefited the Turkestan Muslim community by made cooperation with Germany to fight The Stalin regime. The cooperation between Germany and Turkestan Muslim community marked by forming Germany voluntary soldier with a special member from Turkestan’s Muslim community named TurkestanLegion. Not only used by Germany in fighting in the Soviet Union, but Turkestan Legion also took part in the fighting in Western Front faced England and the United State of America in Normandy.